2013
DOI: 10.1194/jlr.p034520
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in skeletal muscle after an acute intravenous GH bolus in human subjects: identification of a mechanism regulating ANGPTL4

Abstract: This article is available online at http://www.jlr.org suppressed postprandial levels and increased activity during fasting and exercise. Following exposure to a physiological intravenous GH bolus, distinctive temporal changes in substrate fl uxes are recorded in skeletal muscle, characterized by reversible suppression of glucose uptake that peaks after 2 h together with increased uptake of lipids ( 2 ). Triglycerides (TG) in lipoproteins are hydrolyzed to FFA by lipoprotein lipase (LPL) before entering the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Notably, stimulation with GH does not increase lipolysis in explants of human AT (Fain et al 2008) or isolated human adipocytes (Marcus et al 1994), but the sensitivity toward b-adrenergic agonists is enhanced by the presence of GH in the culture medium (Marcus et al 1994). In line with this, it has recently been demonstrated that GH administration in human subjects increases ANGPTL4 levels in plasma (Clasen et al 2013). Given the permissive effect of this protein on cAMP-mediated lipolysis, it seems likely that elevations in systemic ANGPTL4 levels could be one of the mechanisms by which GH stimulates AT lipolysis.…”
Section: Growth Hormonementioning
confidence: 74%
“…Notably, stimulation with GH does not increase lipolysis in explants of human AT (Fain et al 2008) or isolated human adipocytes (Marcus et al 1994), but the sensitivity toward b-adrenergic agonists is enhanced by the presence of GH in the culture medium (Marcus et al 1994). In line with this, it has recently been demonstrated that GH administration in human subjects increases ANGPTL4 levels in plasma (Clasen et al 2013). Given the permissive effect of this protein on cAMP-mediated lipolysis, it seems likely that elevations in systemic ANGPTL4 levels could be one of the mechanisms by which GH stimulates AT lipolysis.…”
Section: Growth Hormonementioning
confidence: 74%
“…However, manipulating hematocrit levels within the physiologically relevant limits in humans did not lead to significant alterations in gene expression, even though we covered a broad spectrum of possible physiological changes. The method we used (Human Gene 1.0 ST Array) detected altered skeletal muscle gene expression 120 minutes after growth hormone treatment and after 72‐hour fasting (Vendelbo et al ., unpublished data), thus validating the method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition it has been reported that GH increases phosphorylation of STAT-5b in human muscle and fat (8) and activates SOCS1-3, CISH, and IGF1 mRNA expression in skeletal muscle (4,9,10). Stress conditions such as exercise and fasting with increased GH secretion have also been shown to stimulate human skeletal muscle STAT-5b phosphorylation and IGF1 mRNA expression (11,12), although it is unclear whether this involves stimulation of SOCS/CISH transcription.…”
Section: Introductionmentioning
confidence: 99%
“…In adipocytes and skeletal muscle, STAT-5b serves as a transcription factor for target genes including a family of cytokine-inducible suppressors of cytokine signaling (SOCS) (1,2,3), cytokine inducible SH2-containing protein (CISH) (2,4), and insulin-like growth factor 1 (IGF1). GH has important actions to regulate anabolic signals and preserve lean body mass protein (1); some of these anabolic effects are mediated by stimulation of lipolysis (5,6).…”
Section: Introductionmentioning
confidence: 99%